Comparative efficacy of Bentonite clay, activated charcoal and Trichosporon mycotoxinivorans in regulating the feed‐to‐tissue transfer of mycotoxins. (16th August 2017) - Bhatti, Sheraz Ahmed; Khan, Muhammad Zargham; Hassan, Zahoor Ul; Saleemi, Muhammad Kashif; Saqib, Muhammad; Khatoon, Aisha; Akhter, Masood
Abstract: BACKGROUND: Mycotoxins contamination in animal products and by‐products is a persistent threat to the food and feed industry. The present study was designed to evaluate the comparative inhibitory effects of Bentonite (BN), activated charcoal (AC) and a newly discovered yeast, Trichosporon mycotoxinivorans (TM), against feed‐to‐tissue transfer of mycotoxins. RESULTS: A dose dependent increase as determined by HPLC, in the residues of aflatoxin B1 (AFB1) and ochratoxin A (OTA) was exhibited in the groups of birds fed AFB1 and OTA alone. The dietary addition of BN and AC to AFB1‐contaminated diets resulted in a 41–87% and 16–72% decrease in AFB1 residues in liver of the birds, respectively. However, this decrease was non‐significant with addition of TM as AFB1 binder. A partial to non‐significant protection was observed by dietary BN and AC, against OTA residues, while a significant decrease in OTA residues (38–84%) was noted in TM‐OTA co‐fed groups. CONCLUSION: The order of efficacy in terms of lowering AFB1 residues in the liver was BN > AC > TM, while against OTA it was TM > BN > AC. The findings of present study suggest that, based upon the nature of target mycotoxins, a mixture of multi‐mycotoxins binders/detoxifiers should be incorporated in the animal feeds. © 2017 Society of Chemical Industry